Dynamics of Social Media Users in Responding to Transgender Freedom (Case Study of #I’mAproudTranswoman on Twitter) - Putridinanti, Maudy Marditta (Universitas Muhammadiyah Surakarta, 2021)
Purpose :Transwomen or transgender woman is someone who was born as a man but then changes herself as a woman. The existence of transwomen in Indonesia is still controversy among the public, as evidenced by the support and scope for them to come out or freely stated about their sexual orientation, such as through social media. However, transwomen’s existences has not been recognize yet. Most of Indonesian people are stick to the eastern culture, even though some people are starting to open up support for transwomen rights. It is trigger the rise of cyberbullying or acts of bullying on social media for those who dare to reveal the identity of sexual orientation. The study aims to analyse the dynamics that occur in social media users responding to the freedom of transwomen in the #I’mProudTranswomen case. Methodolody :Descriptive qualitative research method is used in answering the problem formulation. The author uses analysis on the theory of Encoding and Decoding in analyzing the dynamics of meaning construction in accepting transwomen. Result :The results found that social communities experience structured dynamics from how to interpret the existence of trans women in the media, namely the audience enters into a dominant position, negotiates, and is also in opposition. The results are concluded from the audience’s response to the tweets that Ian Hugen conveyed on his social media platform, namely Twitter, the audience’s understanding and acceptance he existence of Transwomen based on the religious understanding and belief of the audience, the audience’s knowledge of human rights who are free to make life choices and the audience. who position themselves as a minority group that has no place in society.